2017
DOI: 10.1002/jqs.2984
|View full text |Cite
|
Sign up to set email alerts
|

Widespread, episodic decline of alder (Alnus) during the medieval period in the boreal forest of Europe

Abstract: We report pollen‐stratigraphical evidence for an abrupt, episodic and widespread population decline of alder (Alnus), one of the most common boreal tree genera, during the medieval period in northern Europe. Decline of alder pollen values was observed both in forest hollow pollen records reflecting local vegetation of pristine forests and in pollen percentage and pollen accumulation data from lake sediments. The event began roughly at AD 600 and the recovery took place at AD 1000. Human impact is an unlikely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…2b, 4). These ecological processes agree well with the data on climatic changes around the 9th-10th centuries from the Medieval Climate Anomaly, including longlasting droughts (Helama et al 2009;Büntgen et al 2011) and a widespread Alnus decline most probably caused by a sequence of climatic events detrimental to alder followed by a pathogen attack (Stivrins et al 2017;Latałowa et al 2019).…”
Section: Natural Conditions Before the Development Of The Townsupporting
confidence: 87%
See 1 more Smart Citation
“…2b, 4). These ecological processes agree well with the data on climatic changes around the 9th-10th centuries from the Medieval Climate Anomaly, including longlasting droughts (Helama et al 2009;Büntgen et al 2011) and a widespread Alnus decline most probably caused by a sequence of climatic events detrimental to alder followed by a pathogen attack (Stivrins et al 2017;Latałowa et al 2019).…”
Section: Natural Conditions Before the Development Of The Townsupporting
confidence: 87%
“…In the studied profiles, the aquatic indicators are replaced by taxa typical of mires (Figs. 2b,3,4). This change left a distinct signature in several profiles in a form of hiatuses occurring at the transition between limnic sediments and peat (Święta-Musznicka and Latałowa 2016).…”
Section: Natural Conditions Before the Development Of The Townmentioning
confidence: 97%
“…Huttunen (1980) notes that the Evo region, where Naava and Kämmekkä hollows are located, comprises only 1-2% arable land and slash and burn cultivation with the clearing of forest for agricultural purposes was carried out rarely, whereas around 20 km towards the south at Lammi, the land becomes more fertile and as such more suitable for cultivation. In line with this, Stivrins et al (2017) showed that the first crop pollen indicating agricultural practices appeared only 400 years ago at Naava and Kämmekkä hollow, while in other areas of Finland, an intensification of slash and burn activity can be seen in the charcoal records after 1000 cal yr BP due to the expansion of cultivation and establishment of more permanent settlements (Alenius et al, 2013;Lagerås, 1996;Taavitsainen et al, 1998).…”
Section: Fire-events In the Northern European Boreal Forestmentioning
confidence: 83%
“…In addition, we used a biostratigraphic correlation to define the lowermost age of Kämmekkä hollow, based on Naava hollow and Picea expansion in southern Finland (Table 1; Supplementary material 1; Seppä et al, 2009a;Stivrins et al, 2017).…”
Section: Sediment Dating and Age-depth Modelsmentioning
confidence: 99%
“…novērojams alkšņu daudzuma pieaugums -notiek atkopšanās process. Svarīgi atzīmēt, ka identiska tendence vērojama arī alkšņu biomasas izmaiņās Somijā un Polijā (Stivrins et al, 2017;Latałowa et al, manuscript). Ņemot vērā nogulumu datēšanas kļūdas var pieņemt, ka konkrētā alkšņu samazinājuma epizode notikusi vienlaicīgi plašā teritorijā no boreālās līdz pat nemorālās zonas mežiem.…”
Section: Rīgas ūDenskrātuves Fitoplanktons Ivars Druvietisunclassified